(untitled) (Punyawati Journal, 2026)
Financial literacy includes knowledge, skills, attitudes, and practices that contribute to financial well-being for an individual. The rising complexity of financial instruments has changed the financial sector completely. The financial illiteracy of a significant part of the Nepalese community is an impediment to building wealth; financial illiteracy compromises financial security. The objective of this research is to determine the level of financial literacy in terms of the four knowledge areas: knowledge, attitude, behavior, and risk tolerance, for different demographic features such as age, educational status, and financial status. An online survey with multiple-choice questions and five-point Likert scales was employed to collect data and opinions of respondents for descriptive and comparative research methodology. An analysis of variance and descriptive statistics was conducted to analyze 304 valid responses. The findings show that a better status in terms of the four knowledge areas: knowledge, attitude, behavior, and risk tolerance is established. Consequently, financial literacy differs across different demographic features. There is no significant difference in financial knowledge, behavior, and attitude amongst the different groupings. The financial risk tolerance for different groupings is significantly varied by age factor. The educational status is also statistically different for the plan of financial knowledge, attitude, as well as risk tolerance, whereas financial behavior remains less affected. As far as income is concerned, it differs significantly in financial knowledge but not in financial behaviour, attitude, and risk tolerance. The study underlines the exigencies of multi-channel, age-, and education-tailored financial education to support long term planning and risk-aware outcomes.